BIM for project managers : digital construction management - Barnes, Peter, 1954- (ICE Publishing, 2020)
BIM for Project Managers is a concise practical guide which shows how cutting-edge BIM related technologies can facilitate the successful management of construction and infrastructure projects.
Also issued in print: 2020.
Keywords: Building information modeling.; Construction industry -- Management.; Project management.; elektronické knihy; electronic books